International Advertising: Strategic and Cultural Insight from practitioners based in the United Arab Emirates - Rapallo, Alex (2012)
The debate surrounding standardized versus localized advertising still remains at large. Scholars and practitioners appear to reside in three schools of thought including: standardization, adaptation and contingency approach. Many advertising failures occur due to a lack of attention to cultural differences throughout the world. Understanding cultural values with in nations has become a prerequisite for many companies. Research is beginning to highlight the impact religion can have on advertising techniques and the consumer's perception of advertisements. Understanding the impact religion can have on advertising is becoming particularly necessary in the emerging Arab markets where the dominant belief system is Islam. Increasing modernity and Western presence has meant that Muslim societies are being exposed to an increasing amount of media and consumption ideals. This papers answers calls for more studies to focus on the process behind international advertising and the impact of culture and religion, in a context heavily neglected by current research. This research investigation draws upon predominantly qualitative research, analysing 14 international advertising practitioners based in the United Arab Emirates (UAE). The aim of this research was to explore the intentions of advertising and marketing communication managers based in the UAE and their attitudes towards international advertising in the MENA (Middle East and North Africa) region. To evaluate this aim and draw significant conclusions, analysis was broken down into three objectives fundamentally based on advertising standardization intentions, cultural issues and the presence of tradition. The empirical study mainly concluded that respondents implement a contingency based approach to international advertising in the MENA region and that certain cultural factors influence the process of advertising in the Arab markets. Legislation was perceived less of an issue as practitioners relied upon their own cultural intuition. Lastly, attitudes suggest a new future-orientation approach to advertising in the region appears to be on the rise. Managerial implications and directions for future research are also discussed.